DERMATOLOGICAL MANIFESTATIONS OF POLYCYSTIC OVARY SYNDROME - Martins , Gabriela de Souza; Almeida, Joaquim Adriano Antunes de; Trigueiro, Ana Paula Mendes Macedo; Alexandrino, Daiana Bettanin de Melo; Albuquerque, Fernanda de Queiroz; Junqueira , Júlia Ferreira; Silva , Guilherme Augusto Santana; Souza , Thais Heloan de; Ribeiro, Gabriela de Freitas; Cavalcante , Thiago Arruda Prado; Sampaio, Kenneth Candeira; Poleto , Guilherme Guimarães de Paula; et al. (Brazilian Journal of Implantology and Health Sciences, 2024)
Polycystic ovary syndrome (PCOS) is one of the most common endocrine conditions in women of reproductive age, characterized by hormonal imbalances, ovulatory dysfunction, and multiple ovarian cysts. In addition to gynecological symptoms, PCOS can also present significant dermatological manifestations, which affect not only the appearance, but also the quality of life of patients. These manifestations include hirsutism, acne, alopecia and skin pigmentation, among others. Understanding the relationship between PCOS and its dermatological manifestations is crucial for early diagnosis and adequate management of the condition. Objective: To analyze and synthesize recent scientific literature on dermatological manifestations associated with polycystic ovary syndrome, highlighting its prevalence, clinical characteristics and therapeutic approaches. Methodology: The systematic review was conducted in accordance with PRISMA guidelines. Searches were carried out in the PubMed, Scielo and Web of Science databases, limited to articles published in the last 10 years, using the descriptors "polycystic ovary syndrome", "dermatological manifestations", "hirsutism", "acne", "alopecia" . The inclusion criteria were original human studies, in English or Portuguese, that investigated dermatological manifestations in patients with PCOS. Exclusion criteria were animal studies, case reports and narrative reviews. Results: The analysis of the selected studies revealed a high prevalence of dermatological manifestations in patients with PCOS, with hirsutism and acne being the most common. Factors such as insulin resistance and hyperandrogenism play an important role in the development of these manifestations. Several therapeutic approaches, including hormonal agents and insulin modulators, have been investigated for the management of these symptoms. Conclusion: This review highlights the importance of identifying and adequately treating dermatological manifestations in PCOS, aiming not only to improve aesthetics, but also the quality of life and overall health of patients. Early recognition of these symptoms can lead to effective interventions and better long-term clinical outcomes.